Does Parental Mediation of Technology Use Moderate the Associations between Cyber Aggression Involvement and Substance Use? A Three-Year Longitudinal Study - Wright, Michelle F; Wachs, Sebastian (International journal of environmental research and public health, 2019)
The goal of this three-year longitudinal study was to examine the buffering effect of parental mediation of adolescents' technology use (i.e., restrictive, co-viewing, and instructive) on the relationships among cyber aggression involvement and substance use (i.e., alcohol use, marijuana use, cigarette smoking, and non-marijuana illicit drug use). Overall, 867 (Mage = 13.67, age range from 13-15 years, 51% female, 49% White) 8th grade adolescents from the Midwestern United States participated in this study during the 6th grade (Wave 1), 7th grade (Wave 2), and 8th grade (Wave 3). Results revealed that higher levels of Wave 2 instructive mediation weakened the association between Wave 1 cyber victimization and Wave 3 alcohol use and Wave 3 non-marijuana illicit drug use. The relationship was stronger between Wave 1 cyber victimization and Wave 3 alcohol use and Wave 3 non-marijuana illicit drug use when adolescents reported lower levels of Wave 2 instructive mediation. At lower levels of Wave 2 instructive mediation, the association between Wave 1 cyber aggression perpetration and Wave 3 non-marijuana illicit drug use was stronger. Implications of these findings are discussed in the context of parents recognizing their role in helping to mitigate the negative consequences associated with adolescents' cyber aggression involvement.
Keywords: Aggression; Substance-Related Disorders; středozápad USA; Crime Victims; cyber victimization; mužské pohlaví; Longitudinal Studies; longitudinální studie; důvěrnost informací; ženské pohlaví; Parents; Cyberbullying; Confidentiality; rodiče; parental mediation; lidé; Female; substance use; oběti zločinu; Humans; cyber aggression; mladiství; kyberšikana; poruchy spojené s užíváním psychoaktivních látek; Adolescent; Midwestern United States; agrese; Male